Fast fashion: strategy for conquest of global maket (ModaPalavra e-periódico, 2008)
The concept of fast fashion if becomes each more important time for the retail of world-wide fashion that it aims at to take care of more to the informed individuals of the present time that they are each time more eager for the consumption and in fashion terms. The Zara was one of the first ones to introduce fast fashion as strategy of vendas that it has if showing as one forms dynamics of growth of the invoicing of the company and of its recognition in the global market.
Keywords: market; Zara; fast fashion